České ekvivalenty nové ruské frazeologie - Mokienko, Valerij M. (Bohemistyka, 2020)
The article discusses the problems of equivalence in the transfer of Russian phraseological neologisms into Czech. Such an analysis is based on the material of the Russian-Czech dictionary of neologisms compiled by L. Stepanova and M. Dobrova and published at the Olomouc University. A typology of phraseological equivalents, used by the authors of the dictionary, is proposed, the effectiveness of the transfer of phraseological units into the Czech language is demonstrated. A feature of phraseological neologisms of the source language is its original imagery and expressiveness, which makes the task of selecting equivalents especially difficult.